Investigation of Antioxidant from Extracts Leaf, Stem, Fruit of Morinda citrifolia - KHOUNVILAY, Bounthieng; SALITXAY, Timnoy; LOKHAMHEUANG, Vonesy; PHOVISAY, Somsay; BANDAVONG, Viraxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study aimed to investigate of antioxidant from extracts leaf, fruit and stem of noni (Morinda citrifolia L.). The objective method of extracts different solution and antioxidant. Random samples was drying by hot air oven at 50 Celsius degree, blend and extracts by 80% Ethanol, 80% Methanol and antioxidant activity using DPPH radical scavenging method of analyze experiment method CRD(Complete Randomized Design) that 3repeats and 3 treatments for T1=leaf, T2=stem, T3= fruit. The results indicated that sample of Morinda citrifolia L. extracts showed the highest total phenolic content(TP), total tannin(TA) and total flavonoid content(TF) of 4.92 ±0.27mg GAE/g, 3.61 ±0.21 mg TAE/g, 1.23 ±0.85mg QE/g, respectively. The antioxidant activity using DPPH radical scavenging method extracts of leaf, fruit and stem of Morinda citrifolia L. showed the highest antioxidant activity with IC50 values of 5.00 ±0.31mg/g. It was found that the condition middle leaf noni TP more 9.41±0.58mg GAE/g D.W; older leaf noni TA more 4.61±0.04 mgTAE/g D.W; middle leaf noni TF more 1.86±0.05mg QE/g D.W, the antioxidant activity using DPPH radical scavenging activity found in middle noni more 8.82±1.64 mg/g, respectively. Concluded that antioxidant activity extracted from different parts of Morinda citrifolia L. is important to be developed as a health supplement to help reduce free radicals that are problematic for people's health.